IMPLEMENTATION OF E-LEARNING USING THE MOODLE - Melyanti, Rika; Febriani, Anita (Jurnal Pendidikan Teknologi Kejuruan, 2021)
STAI Tuanku Tambusai Pasir Pangaraian is a high school for Islamic religious education, which in the Teaching and Learning Process (PBM) is currently trying to apply the concept of blended learning by using e-learning. The purpose of this research is to build a Learning Management System (LMS) that can assist lecturers and students in conducting PBM with the help of computer technology. This is felt to have become a necessity during the pandemic and industrial revolution 4.0, STAI should have an e-larning that is able to answer challenges. The online learning system service architecture (e-learning) can be used as an appropriate design in the development of learning methods where the level of flexibility, scalability and functionality can make PBM easier to do anywhere and anytime. The designed online learning system (e-learning) at STAI Tuanku Tambusai is used by two actors, namely students and lecturers.